ANALISIS PERBEDAAN KINERJA KEUANGAN PENDAPATAN ASLI DAERAH PEIODE OPINI NON WTP DAN PERIODE OPINI WTP (Studi Pada Kabupaten/Kota di Provinsi Aceh Tahun 2013-2014) - Yuni Wulan Dari; M Rizal Yahya (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The purpose of this study is to examine and analyze the differences in financial performance of local revenue (PAD) during the periods of non unqualified opinion and unqualified opinion among districts/municipalities within Aceh Province Aceh in 2013-2014. Population of the study is 23 districts/municipalities of Aceh province. Using purposive sampling technique, 10 districts/municipalities were choosen as the sample of the study according to the criteria that those districts/municipalities should have audit opinion improvement, from non unqualified in 2013 became unqualified in 2014. The data used was the budget realization statement of each district/municipality for the year 2013-2014. Paired sample t-test was used to analyze the data.The results of the study showed that the financial performance of local revenue (PAD) during non unqualified opinion period have no different compare to qualified opinion period in districts/municipalities of Aceh Province for the year 2013-2014. In the aspect of the degree of fiscal decentralization and financial independence ratio, financial performance of local revenue during non unqualified period differs from unqualified period. In addition, based on the effectiveness and growth of local revenue ratios, financial performance of local revenue in districts/municipalities of Aceh Province have no different within these two periods. Keywords: Financial Performance, Local Revenue (PAD), Audit Opinion, Degree of Fiscal Decentralization, Effectiveness of Local Revenue (PAD) Ratio, Growth of Local Revenue (PAD) Ratio, and Financial Independence Ratio.